Clinical Study the Relationship Between High-TSH Degree and Changes of LDL-C in Yunnan Plateau (China) Pregnant Patients’ Serum - Li, Bin; Yan, Kong; Meng, Tian (International Journal of Innovative Research in Medical Science, 2023)
Objective: It was to investigate the relationship between high thyrotropin, thyroid stimulating hormone (TSH) degree and changes of low-density lipoprotein cholesterol (LDL-C) in Yunnan Plateau pregnant patients’ serum in China; Methods: All pregnant woman were collected from the Kunming Angel Women's and Children's Hospital from January 2021 to October 2022, who were diagnosed by the endocrinology department, during their pregnancy. Then it analyzed their biochemical indicators levels and blood liquid parameters changes in their serum. Additionally, we investigated their epidemiological data, including the treatment history of hypothyroidism; Results: High-TSH degree and increasing of LDL-C level were both risk factors leading to hypertension, cardiovascular symptoms, symptoms of digestive tract, pregnancy ultrasound indicating small-sized fetus (P＜0.05). Importantly, they reinforce each other on patients. Their increasing caused gestational diabetes mellitus, preterm birth history and autoimmune diseases in Yunnan plateau (China). TSH≥4.3 m IU/L and DL-C≥3.6 mmol/L in the pregnant patients’ serum, which were approved by obstetric professional committee of that Hospital. Furthermore, only in high-TSH degree group, their high cholesterol could cause premature birth, elevated blood sugar, high blood pressure prenatal, postpartum infection and preeclampsia (P＜0.05); Conclusion: These risk factors (high-TSH and LDL-C changes) could affect the health of pregnant, maternal and fetal, which should be taken to manage it so as to improve the perinatal health.